ВПЛИВ ОСВІТИ НА ФОРМУВАННЯ КРЕАТИВНОГО ЛЮДСЬКОГО КАПІТАЛУ (International Journal of Innovative Technologies in Economy, 2018)
The article describes the influence of education on the formation of creative human capital. It is justified that education has a significant impact on the formation, reproduction and development of creative human capital. The paper also analyzes the state of the educational level of citizens and innovative development in Ukraine compared to other countries of the world. The work states that it is necessary to reform the modern educational system in order to provide the appropriate level of training of professionals, in which knowledge, skills and abilities will meet the requirements of the creative economy. As recommendations the article presents the main directions of the modern system of education that will be able to provide effective formation of creative human capital, in particular: creation of conditions for development of creative, independent and socially responsible person who is professionally competent; integration of educational and cultural components, a combination of training, education and research work; development of a creative environment that stimulates pupils and students to form an active life position in order to implement their personal and creative potential.